Loss of submerged macrophytes in shallow lakes alters bacterial and archaeal community structures, and reduces their co-occurrence networks connectivity and complexity - Liu, Jiahui; Huang, Xianfei; Jiang, Xin; Qing, Chun; Li, Yue; Xia, Pinhua (Frontiers in Microbiology, 2024)
Bacteria and archaea are important components in shallow lake ecosystems and are crucial for biogeochemical cycling. While the submerged macrophyte loss is widespread in shallow lakes, the effect on the bacteria and archaea in the sediment and water is not yet widely understood. In this study, 16S rRNA gene sequencing was used to explore the bacteria and archaea in samples taken from the sediment and water in the submerged macrophyte abundant (MA) and submerged macrophyte loss (ML) areas of Caohai Lake, Guizhou, China. The results showed that the dominant bacterial phyla were Proteobacteria and Chloroflexi in the sediment; the dominant phyla were Proteobacteria, Actinobacteriota, and Bacteroidota in the water. The dominant archaea in sediment and water were the same, in the order of Crenarchaeota, Thermoplasmatota, and Halobacterota. Non-metric multidimensional scaling (NMDS) analyses showed that bacterial and archaeal community structures in the water were significantly affected by the loss of submerged macrophytes, but not by significant changes in the sediment. This suggests that the loss of submerged macrophytes has a stronger effect on the bacterial and archaeal community structures in water than in sediment. Furthermore, plant biomass (PB) was the key factor significantly influencing the bacterial community structure in water, while total nitrogen (TN) was the main factor significantly influencing the archaeal community structure in water. The loss of submerged macrophytes did not significantly affect the alpha diversity of the bacterial and archaeal communities in either the sediment or water. Based on network analyses, we found that the loss of submerged macrophytes reduced the connectivity and complexity of bacterial patterns in sediment and water. For archaea, network associations were stronger for MA network than for ML network in sediment, but network complexity for archaea in water was not significantly different between the two areas. This study assesses the impacts of submerged macrophyte loss on bacteria and archaea in lakes from microbial perspective, which can help to provide further theoretical basis for microbiological research and submerged macrophytes restoration in shallow lakes.